Auster’s “Album” in Report from the Interior: Analysis and Analogies - Richard PHELAN (E-REA)
The article is devoted to the final section of Paul Auster’s 2013 Report from the Interior. We first attempt to imagine the various ways readers integrate the “Album” of images into their experience of the book. Then we go on to examine the role of the visual images in the journey of memory between interior and exterior, and the way these visual images relate to the questions of visibility and disappearance that animate the book. How do such non-personal, medium-quality images mediate memory? The article seeks, finally, to account by analogy for the elaboration and the esthetic effects of this trans-disciplinary work.